Mirror, Mirror on the Wall: Culture's Consequences in A Value Test of its Own Design - Ailon, Galit (Academy of Management Review, 2008)
The paper offers a critical reading of Geert Hofstede's (1980) Culture's Consequences using an analytical strategy where the book is mirrored against itself and analyzed in terms of its own proposed value dimensions. “Mirroring” unravels the book's normative viewpoint and political subtext and exposes discursive interests in its research process. Making all this evident in the canonical book's own terms, this paper communicates critical concerns across paradigm boundaries. It indicates the need to reconsider concepts and convictions that predominate cross-cultural research and to adopt norms of reflexivity that transcend existing notions of “cultural relativism.”